The Important Role of Endoscopy in Management of Pediatric Pseudomembranous Necrotizing Tracheitis - Wu, Xiling; Wu, Lei; Chen, Zhimin (Frontiers in Pediatrics, 2020)
Pseudomembranous necrotizing tracheitis is a rare, but life-threatening cause of central airway obstruction. Here, we reported three cases of pediatric pseudomembranous necrotizing tracheitis. The infectious etiologies were Staphylococcus aureus secondary to influenza A virus and Aspergillus fumigatus. Endoscopy was used in diagnosis and management of all patients and two patients survived. The improvement in mortality rate of these diseases need early recognition and prompt treatment with mechanical debridement by endoscope and early initiation of broad spectrum antibiotics. Endoscopy is a promsing tool to diagnose and remove the pseudomembrane, therefore relieving central airway obstruction.